The effect of high temperature on kinetics of reactive species generation in patients with type 2 diabetes - Tikhonova, Irina V.; Grinevich, Andrei A.; Kosyakova, Ninel I.; Safronova, Valentina G. (Free radical biology & medicine, 2022)
The excessive amount of reactive species under chronic inflammation, which are accompanied by an increase body temperature, lead to diabetic complications. Phagocyte NADPH oxidase is the key enzyme in these processes. The role of high temperature in its regulation in diabetes is not clear. The aim was to investigate the effect of high temperature on NADPH-oxidase-dependent generation of reactive species in diabetic patients. Chemiluminescent method was applied to assess respiratory burst kinetics initiated by opsonized zymosan in blood or phorbol ester in isolated granulocytes. Analyzing ROC curves, the main predictors and changes in stages of activation of NADPH oxidase were determined. Phosphoisoforms of p47phox and p67phox were quantified by immunoblotting. Response to opsonized zymosan was lower in all subjects at 40 °C vs 37 °C, its kinetic parameters (except Tmax) were higher in blood of patients vs controls. Response rate was the main significant predictor to distinguish groups of subjects at 40 °C indicating NADPH oxidase upregulation in diabetes. Ca2+-dependent generation of reactive species by cells increased in both groups at 40 °C vs 37 °C, kinetic parameters were higher in patients. Initial phospho-p47phox level was higher in patient cells vs ones in controls. It was increased by ionomycin, phorbol ester, or 40 °C in control cells and unchanged in patient ones. Phospho-p67phox level was unchangeable in intact cells of healthy donors and patients at both temperatures. Excessive amounts of reactive species in patient cells were the consequence of granulocyte priming due to p47phox phosphorylation. Thus, high temperature decreased phagocytosis- and enhanced Ca2+-dependent generation of reactive species making the differences between controls and patients less pronounced. The effect of temperature on the generation of reactive species in blood granulocytes is associated with activity of NADPH oxidase that can be a prospective therapeutic target for pathologies accompanied by inflammation including type 2 diabetes. [Display omitted] •High temperature promoted low production of reactive species in blood.•The rate of respiratory burst was the most significant predictor.•Ca2+-dependent generation of reactive species by granulocytes was high at 40 °C.•p-p47phox was low in intact healthy donor cells and high in patient ones at 37 °C.•p-p47phox was high in healthy donor cells and unchangeable in patient ones at 40 °C.